I-V model of nano nMOSFETs incorporating drift and diffusion current. (September 2018) - Huang, Heng-Sheng; Wang, Wei-Lun; Wang, Mu-Chun; Chao, Yu-Hao; Wang, Shea-Jue; Chen, Shuang-Yuan
Abstract: The drive current of MOSFETs becomes more and more difficult to be estimated as the device size keeps scaling down. Conventionally, for a long channel device, the surface-channel drift current of MOSFET is considered only, and it is convinced that as the drain voltage increases, the inversion charge density near the drain site is going to decrease and approaches to zero forming the pinch-off point making the total current stop increasing and remain a constant. Thus, the channel current of the MOSFET becomes saturated instead of zero. Because of the drawback of device model in nano short-channel devices, a novel concept is added into this model, including the contribution of surface diffusion current with an assumption, which is the total drive current only composed of surface drift current and surface diffusion current. The mixed current model in simulation and measurement demonstrates the more impressive performance for all channel lengths until 28-nm node. Highlights: The cross-sectional profile of an nMOSFET is clearly re-defined. The contribution of diffusion current in surface channel is included in simulation. The diffusion current in each position of channel is incorporated. The trend of simulation and sense results is consistent. Precisely providing the model of drive current at nano-node process.